Clinical Significance of DPYD Gene Polymorphism Testing in Colorectal Cancer Patients Receiving Fluoropyrimidine-Based Chemotherapy: A Single-Center Study in Latvia - Sofija Vilisova; Aija Gerina (European Scientific Journal, ESJ, 2026)
Background: Fluoropyrimidine-based chemotherapy, including 5-fluorouracil (5-FU) and capecitabine, is a cornerstone of colorectal cancer (CRC) treatment. However, treatment-related toxicity varies substantially among patients and is influenced by pharmacogenetic factors. Variants in the DPYD gene, which encodes the enzyme dihydropyrimidine dehydrogenase (DPD), are associated with reduced enzyme activity and an increased risk of severe toxicity. Aim: To evaluate the prevalence of clinically relevant DPYD polymorphisms in Latvian CRC patients receiving fluoropyrimidine-based chemotherapy and assess the clinical impact of genotype-guided dose adjustment. Methods: This single-center observational study included 46 patients with histologically confirmed CRC treated at Pauls Stradiņš Clinical University Hospital. Patients were divided into retrospective and prospective cohorts. Genotyping was performed for four clinically relevant DPYD variants (c.1905+1G>A, c.1679T>G, c.2846A>T, and c.1236G>A). Clinical data, treatment modifications, and toxicity outcomes were analyzed. Toxicity was graded according to CTCAE criteria. Results: Chemotherapy-related toxicity occurred in 43% of patients, while severe toxicity (grade 3–4) was observed in 13%. Clinically relevant DPYD variants were detected in 2 patients (4.4%), both carrying the c.1236G>A (HapB3) variant. No severe toxicity was observed among variant carriers who underwent genotype-guided dose reduction. Age >70 years was significantly associated with dose reduction (p=0.02), whereas younger patients experienced a higher incidence of severe toxicity (p=0.042). Conclusion: DPYD testing is feasible and clinically relevant in routine oncology practice. The findings support the potential clinical value of genotype-guided treatment strategies in CRC patients receiving fluoropyrimidine-based chemotherapy. However, larger multicenter studies are required to confirm their impact on treatment safety and toxicity reduction.